Fluoroalkyl chloroformates in treating amino acids for gas chromatographic analysis - Husek, Petr; Simek, Petr; Hartvich, Petr; Zahradnícková, Helena (Journal of chromatography. A, 2008)
Novel fluoroalkyl chloroformates with three and four carbon atoms were investigated for the immediate conversion of amino acids into hydrophobic derivatives in water-containing media. Derivatization conditions were extensively studied and optimized sample preparation protocols elaborated. More than 30 amino acids were treated with the particular reagent in isooctane by simply vortexing the reactive organic phase with a slightly basified aqueous medium containing pyridine or 3-picoline as a catalyst. Outstanding separation of nearly all components on 5% phenylmethylsilicone phase in gas chromatographic (GC) analysis with mass spectrometric (MS) or flame ionization detection (FID) required <10 min. Quantitation characteristics involving linearity in the range of 0.1-100 nmol, regression coefficients of 0.999-0.953 (histidine), MS limit of detection (LOD) reaching 0.03 pmol at proline to nearly 20 pmol at glutamic acid, plus electron impact (EI) spectra and diagnostic SIM fragment ions of the derivatives are reported. The novel method is simple, robust and rapid, enabling to treat amino acids in aqueous environment and to analyze them in <15 min.
Keywords: formiáty; aminokyseliny; pyridiny; Amino Acids; pikoliny; Alcohols; plamínková ionizace; Flame Ionization; Formates; plynová chromatografie s hmotnostně spektrometrickou detekcí; Catalysis; Gas Chromatography-Mass Spectrometry; Picolines; katalýza; alkoholy; Pyridines